An unusual case of anaemia and lymphadenopathy in a soldier on deployment. Issue 3 (22nd March 2013) - O'Shea, M K; Gregg, R; Naylor, J
Abstract : We describe the case of a British soldier, originally from southeast Africa, who presented to the British military hospital in Helmand Province, southern Afghanistan, with a history of constitutional upset, profound anaemia and diffuse lymphadenopathy with hepatosplenomegaly. Following evacuation to the UK investigations revealed a rare (and a not so rare) diagnosis. This case raises a number of questions regarding the population at risk, the prevalence of endemic diseases in this population and laboratory capabilities in the deployed setting.